Forms of seguir ‘to keep on’ in Spanish: interactions between continuative aspect and situation type - Jaque, Matías (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This work addresses the expression of continuative aspect in the Spanish construction seguir ‘to continue’+ (non) verbal predicative structure. We propose that the continuative temporal presupposition shows two variants: a strong one, which states that, if a state of affairs holds at a given reference time, then it must have held in at least one prior adjacent time; and a weak one, for which the adjacency condition does not apply and which admits, therefore, temporal ‘gaps’ in an eventuality’s continuity. These variants correlate with the situation type of the predicate that seguir is attached to: while events easily admit a weak presupposition reading, states exhibit the strong one. In empirical terms, we test the hypothesis through a corpus study in which the available readings of seguir clauses modified by adverbial phrases headed by después ‘after/later’ are observed. As expected, ‘suspension’ readings (me desperté pero después seguí durmiendo ‘I woke up but later I kept sleeping’) show up preferently with events. From a theoretical point of view, and following Balashov (2011) and related work, this pattern is accounted for from an ontology in which events are taken as four-dimensional objects with intrinsic duration (perduring objects), as opposed to individuals and states, whose duration is derived from successive instantaneous stages. Events allow a temporally discontinuous way of persistence. States’ persistence, on the other hand, depends on the persistence of the objects manifesting them, which is always built upon a temporally adjacent series of stages.